1999
DOI: 10.1021/jo990484l
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Energetics of the Samarium Diiodide−HMPA Complex in Tetrahydrofuran

Abstract: The role of HMPA as a ligand for SmI2 and the stoichiometry and energetics of formation for the SmI2−HMPA complex in THF were investigated employing UV−vis spectroscopy, isothermal titration calorimetry (ITC), and vapor pressure osmometry (VPO). The aggregation number for SmI2 in THF was found to be 0.98 ± 0.09 over the entire concentration range studied (6.71−84.0 mM), indicating that SmI2 is monomeric. The UV−vis data suggest that four HMPA ligands coordinate to SmI2, and this was supported by ITC experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…6. These overall features of the UV spectra have been described elsewhere [9] , although in that case a substantial decrease in the absorption was noted over the whole wavelength range as HMPA was added. Kinetics of electron transfer processes: Rate constants k obs were measured for the reactions of SmI 2 with 1-iodobutane (Table 1) and with benzyl chloride (Table 2), for various concentrations of HMPA.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…6. These overall features of the UV spectra have been described elsewhere [9] , although in that case a substantial decrease in the absorption was noted over the whole wavelength range as HMPA was added. Kinetics of electron transfer processes: Rate constants k obs were measured for the reactions of SmI 2 with 1-iodobutane (Table 1) and with benzyl chloride (Table 2), for various concentrations of HMPA.…”
Section: Resultssupporting
confidence: 71%
“…[8b] However, the solution structures of the complexes may differ; indeed, isothermal titration calorimetry experiments have indicated that a complex accommodating six HMPA ligands is not thermodynamically favored in THF, even in the presence of large amounts of HMPA. [9] Rather it was suggested that [SmI 2 (hmpa) 4 ] was the reductant responsible for the unique reactivity exhibited by Sm II in all THF/HMPA mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the higher end of the concentration range examined in this study was very close to the solubility limit of SmI 2 in THF, indicating that the reagent is always monomeric under normal reaction conditions. 36 As a consequence, deaggregation is unimportant. Follow-up studies in With the VPO study completed, ITC was used to delineate the stoichiometry of the SmI 2 -HMPA complex and to determine the affinity of HMPA for Sm(II) in THF.…”
Section: Biographical Sketchmentioning
confidence: 99%
“…[34] The concentration of the SmI 2 was determined by iodometric titration. [35] 2-Butanone, 1-chlorobutane, styrene and 4-tolunitrile were purchased from Aldrich and distilled before use. Benzyl-(1-phenylethylidene)amine was synthesized according to a reported procedure.…”
Section: Methodsmentioning
confidence: 99%